Fatigue performance and stress range modeling of SFRC beams with high-strength steel bars. (1st August 2020) - Gao, Danying; Gu, Zhiqiang; Tang, Jiyu; Zhang, Chong
Highlights: The fatigue flexural behaviour of SFRC beams with HRB500 steel bars was studied. Adding steel fibers can improve the fatigue performance of beams significantly. The fiber bridging effect reduced the stress ranges of tensile steel bar. An analytical model was proposed to predict fatigue stresses of tensile steel bars. Abstract: The fatigue performance of steel-fiber-reinforced concrete (SFRC) beams with tensile steel bars of 500 MPa yielding strength (HRB500) was investigated through flexural tests. One control beam was tested to determine the ultimate capacity on being subjected to static loading, and eight beams with variable stress levels and fiber contents were tested subjected to fatigue loading. Test results indicated that the fatigue life of the beams decreased with increasing stress level and increased with fiber content. For an SFRC beam with 1% fiber content, its fatigue life increased by twice compared with that of non-fiber-reinforced concrete beams, thereby, confirming the fact that adding steel fibers into concrete can enhance fatigue life significantly. With the addition of steel fibers, the cracking patterns of the beams improved and deflections decreased during fatigue loading. Furthermore, the stress range of the tensile steel bar decreased with increasing fiber content, and slippage did not occur between the tensile steel bar and concrete owing to adequate anchorage. An effective moment of inertia method that considers the effects of steel fibers was used to calculate the stresses of tensile steel bars in the first loading cycle; subsequently, an empirical expression to calculate the SFRC strain in compression zone under fatigue loading is established. Finally, a prediction model of stress range for the tensile steel bar of SFRC beams under fatigue loading is proposed and further validated through the results of tests on 19 SFRC beams.